Identification and characterization of circular RNA in the model of autism spectrum disorder from PM2.5 exposure - Xie, Xiaoqian; Li, Kang; Liang, Xiaotian; Tian, Lei; Lin, Bencheng; Yan, Jun; Shi, Yue; Liu, Xiaohua; Xi, Zhuge (Frontiers in Genetics, 2023)
PM2.5 induces a series of effects on neurological disorders, including autism spectrum disorder (ASD), however, the mechanism is not completely clear yet. Circular RNAs (circRNAs) are a class of closed-loop structures that can be stably expressed in vivo. Our study aims to investigate the differentially expressed circRNAs (DECs) in PM2.5 exposure-induced ASD-like models. Briefly, Postnatal Sprague-Dawley (PSD) rats were exposed to PM2.5, the hippocampal tissues were collected for circRNA sequencing of the transcriptome. 7770 circRNAs were found and 18 DECs were identified, and the circRNAs with the most significant differences were selected for validation by quantitative real-time polymerase chain reaction (qRT-PCR) and sanger sequencing. The expression changes of circ-Mbd5 and circ- Ash1l were the most significant between the control and exposure groups. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analyses were performed to understand the function of DECs, and DECs were enriched in biological processes associated with ASD. The circRNA-miRNA-mRNA regulatory network depicted by bioinformatics includes 186 genes, and many of them were highly associated with ASD. To our knowledge, this was the first time to elucidate the influence of PM2.5 on ASD from the perspective of circRNAs, which could provide new insights for the mechanism of ASD.